Aluminum and manganese tolerance on wheat (Triticum aestivum L.) Cultivars: V. al and Mn influence and tolerance degree to each element in the Ca uptake - Brauner, J.L.; Sarruge, J.R. (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1980)
The influence of Al, Mn and differential tolerance to those elements in the Ca uptake were studied on excised roots of wheat seedlings, using Michaelis - Menten kinetics. Test cultivars were Sonora 63C, Yecora and IAS 63, respectively, suscetible, intermediate and tolerant to Al, and CNT1, Sonora 63C and IAS 55, respectively, suscetible, intermediate and tolerant to Mn. Labelled 45Ca solutions of CaCl2 ranged 5x1O-6M to 2.56x1O-3M. Solutions of AlCl3 and Mn Cl2 were 10-4M. a) The results showed evidence of two mechanisms on Ca uptake: one operating in the range of 5x10 M to 8x10-5 M (I) and other in the range of 1,6 x 10-4M to 2.56 x 10-3M (II). b) In the range I, Al and Mn inhibited Ca uptake.Range II may inhibit or stimulate Ca uptake, according to the test cultivar. c) In the absence of Al and Mn, cultivars showed intrinsic differences in Ca uptake in range II. Evidences for such differences were not conspicuous in range I. d) In the presence of Al, the Ca uptake was not related to Al tolerance in range I but it was in range II. e) In the presence of Mn, cultivars showed intrinsic differences on Ca uptake on both range I and II. Although, in range II, such differences were not related to Mn tolerance.